A study on the flow interference characteristics of projectiles successively launched underwater. (June 2022) - Gao, Shan; Shi, Yao; Pan, Guang; Quan, Xiaobo
Highlights: A New simulation method, which accurately predict multiphase flow, compressibility of gas, turbulence, and gravity and so on, is established during projectiles launched successively underwater. The hairpin vortex packet in the free wake flow during underwater launch is composed of the multistage hairpin vortex. Through the vortex legs of the free wake flow, hydrodynamic properties of the second projectile have improved. When the second projectile be launched after Δ T = 2 . 0, flow disturbance will disappear during successive underwater launch. Abstract: This paper analyzes the flow interference characteristics of projectiles successively launched underwater with 6 degrees of freedom for different dimensionless launch time intervals and different dimensionless transverse-flow speeds. The realizable k − ε turbulence model and energy equation, as well as the volume of fluid method and overlapping grid technique, are used. Additionally, a verification of the numerical method and a validation of the grid independence are presented. The pressure distribution on the inflow side and backside, the hydrodynamic parameters, the trajectory, and the pitch attitude are studied with the focus on the evolution of hairpin vortex packets in free wake flow. The results show that the hairpin vortex packet in the free wake flow is composed of a multistage hairpin vortex and a low-speed streak region with a stream scale that runs along the interior of the hairpin vortex packet. At higher transverse-flow speeds, the pressure coefficient and hydrodynamic coefficient of the second projectile increase as the launch time interval increases. Due to the effects of transverse flow, when the secondary projectile passes through the core region of the wake vortex, the pressure of uneven distribution characteristics greatly reduces and the trajectory stability increases. To maximize the efficiency and success rate of projectiles successively launched underwater, the second projectile should be launched at Δ T = 2 . 0 .